How to Represent Female Identity on the Restoration Stage: Actresses (Self) Fashioning - Serrano González, Raquel; Martínez-García, Laura (International Studies. Interdisciplinary Political and Cultural Journal, 2014)
Despite the shifting ideologies of gender of the seventeenth century, the arrival of the first actresses caused deep social anxiety: theatre gave women a voice to air grievances and to contest, through their own bodies, traditional gender roles. This paper studies two of the best-known actresses, Nell Gwyn and Anne Bracegirdle, and the different public personae they created to negotiate their presence in this all—male world. In spite of their differing strategies, both women gained fame and profit in the male—dominated theatrical marketplace, confirming them as the ultimate “gender benders,” who appropriated the male role of family’s supporter and bread-winner.